Cognition, language and aging - Wright, Heather Harris (John Benjamins Publishing Company, 2016)
Age-related changes in cognitive and language functions have been extensively researched over the past half-century. The older adult represents a unique population for studying cognition and language because of the many challenges that are presented with investigating this population, including individual differences in education, life experiences, health issues, social identity, as well as gender. The purpose of this book is to provide an advanced text that considers these unique challenges and assembles in one source current information regarding (a) language in the aging population and (b) current theories accounting for age-related changes in language function. A thoughtful and comprehensive review of current research spanning different disciplines that study aging will achieve this purpose. Such disciplines include linguistics, psychology, sociolinguistics, neurosciences, cognitive sciences, and communication sciences.